Between Punishment and Rehabilitation: Judicial Reasoning in Narcotics Adjudication under Article 114 of Indonesia’s Narcotics Law - Alief Raihan; Kadek Wiwik Indrayanti; Hatarto Pakpahan (International Journal of Social Sciences, Language, and Education, 2026)
This study examines the legal basis of judicial reasoning in Judgment No. 183/Pid.Sus/2025/PN.Mlg concerning the application of Article 114 of Law No. 35 of 2009 on Narcotics and evaluates its consistency with contemporary principles of justice. The research employs a normative legal method using statutory and case approaches. Primary legal materials consist of the Narcotics Law, Law No. 1 of 2023 concerning the Criminal Code, Law No. 39 of 1999 concerning Human Rights, and relevant judicial decisions. The analysis focuses on the normative qualification adopted by the court, the structure of judicial reasoning, and the implications of the judgment for substantive justice and human rights protection. The findings indicate that the court emphasized formal legal interpretation while providing limited consideration of the rehabilitation mandate contained in Articles 54 and 103 of the Narcotics Law. Evaluation through the theories of John Rawls, Emile Durkheim, and Gustav Radbruch suggests that the judgment prioritizes procedural legality over proportionality, social reintegration, and substantive justice. The study argues for a stronger rehabilitation based approach, greater integration of restorative justice principles, and criminal law reforms that harmonize legal certainty with human rights protection in narcotics adjudication.